Excised Abdominoplasty Material as a Systematic Plastic Surgical Training Model - Demirseren, M. Erol (Hindawi Publishing Corporation, 2012)
Achieving a level of technical skill and confidence in surgical operations is the main goal of plastic surgical training. Operating rooms were accepted as the practical teaching venues of the traditional apprenticeship model. However, increased patient population, time, and ethical and legal considerations made preoperation room practical work a must for plastic surgical training. There are several plastic surgical teaching models and simulators which are very useful in preoperation room practical training and the evaluation of plastic surgery residents. The full thickness skin with its vascular network excised in abdominoplasty procedures is an easily obtainable real human tissue which could be used as a training model in plastic surgery.